Lean principles for streamlining loan management process - Lappalainen, Iina (My University, 2019)
Financial sector is experiencing remarkable changes and there has arisen a need to improve operational efficiency. To respond to the new situation, financial service providers have become interested in various management philosophies. One of these philosophies is lean, which has previously been used mostly in the manufacturing sector. Its core idea is to create value by eliminating wasteful activities from a process. Efficiency can also be increased with new digital solutions such as automation. In order to successfully adopt automation, organizations need to consider that their processes are optimally designed for the software. This thesis has studied a corporate loan management process of a financial service provider (case organization) and how this process could be streamlined by using lean principles. Simultaneously, the thesis has observed how lean could be applied in the financial sector in general, not to forget the overall service context. Besides mapping the loan process based on lean, this thesis has tackled the question regarding automation and how it could be used to further improve the loan process. The thesis has been carried out as an empirical, qualitative case study with the constructive research approach. The data was collected by interviewing six employees at the case organization and through observation. Based on these findings, the researcher analyzed the current state of the loan process. After that, the construction was built drawing together the current state and theoretical background. The construction suggests improvements to the loan process, and it was presented in the case organization twice. Based on the feedback, the construction was developed and modified. When reflecting the theoretical background of lean philosophy into the researched loan process, one can say that lean can be applied into service context. There were multiple inefficiencies within the loan process, that could be identified based on the original classifications in the lean theory. The observed loan process was thought to be standardized even though there were elements signaling the quite opposite. Standardization is one of the key factors to enable process automation, and thus the loan process should be streamlined before it can be automated. However, there are smaller manual tasks where automation could be used. Overall, lean provides multiple tools for the loan process improvement, but it is vital to understand that in order to thrive for a long-term improvement, lean should be understood as an organization wide culture.
Keywords: Lean, automaatio, lainanhallinta, rahoitusala, prosessisuunnittelu